The mouse olfactory peduncle. 3. Development of neurons, glia, and centrifugal afferents - Brunjes, Peter C.; Collins, Lindsay N.; Osterberg, Stephen K.; Phillips, Adriana M. (Frontiers in Neuroanatomy, 2014)
The present series of studies was designed to provide a general overview of the development of the region connecting the olfactory bulb to the forebrain. The olfactory peduncle contains several structures involved in processing odor information with the anterior olfactory nucleus (cortex) being the largest and most studied. Results indicate that considerable growth occurs in the peduncle from postnatal day (P)10-P20, with reduced expansion from P20-P30. No evidence was found for the addition of new projection or interneurons during the postnatal period. GABAergic cells decreased in both number and density after P10. Glial populations exhibited different patterns of development, with astrocytes declining in density from P10-P30, and both oligodendrocytes and microglia increasing through the interval. Myelination in the anterior commissure emerged between P11-14. Dense cholinergic innervation was observed at P10 and remained relatively stable through P30, while considerable maturation of serotonergic innervation occurred through the period. Unilateral naris occlusion from P1-P30 resulted in about a 30% reduction in the size of the ipsilateral peduncle but few changes were observed on the contralateral side. The ipsilateral peduncle also exhibited higher densities of GAD67- containing interneurons and cholinergic fibers suggesting a delay in normal developmental pruning. Lower densities of interneurons expressing CCK, somatostatin and NPY and in myelin basic protein staining were also observed. Understanding variations in developmental trajectories within the olfactory peduncle may be an important tool for unravelling the functions of the region.